THE SOCIAL AWARENESS IN THE POETRY OF P. K. MISHRA - Pati, Nibedita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In this paper, I have attempted to prepare a bit critical estimation of social awareness in the poetry of Prof. Prafulla Kumar Mishra whose works have been accumulated under the title named Chitrakurangi, Tava nilaye, Brahmanabhih, Konarke, Catvari srnga, Manojangame, Tathapi satyasya mukham, Godhulih, Chaitrarajani etc.